Electronic Microscopic Evaluation of Sodium Sulfonate Effect on Hybrid Layer and Resin Tags Thickness - H Alaghehmand (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: With effect of acidic, basic and neutral soaps in bond strength and microleakage of dentin bonding agents, we found that neutral soap (sodium sulfonate) had the most effective on bond strength increase and microleakage decrease. The aim of this research was microscopic examination of sodium sulfonate effect on thickness of dentin bonding agents hybrid layer and resin tags thickness.METHODS: In this laboratory study, 20 third molar teeth were randomly divided into two groups of ten and their occlusal surface enamel was removed by disc. First group was etched by phosphoric acid 35% and after using of Excite solution, a transparent cylinder with 2mm on height and diameter was put on dentinal surfaces and filled Tetric ceram composite resin and light cured for 40 seconds. In second group after etching and washing, sodium sufonate was rubbed for 30 seconds and washed and subsequent stages have done like first group. After preparation of buccolingual sections all of the samples were put in 6 normal solution of HCL for 8 hours and 1% NaOCL for 10 minutes and studied under electronic microscope. Thickness of hybrid layer and length and diameter of resin tags were calculated.FINDINGS: The length mean of resin tags in second group (16.88±4.71µ) was more than first group (14.31±6.32µ). The diameter mean of resin tags in second group (3.04±0.88µ) was more than first group (2.1±1.3µ). The thickness mean of hybrid layer in second group (15.73±3.69µ) was more than first group (13.66±8.22µ). But there was no significant difference in none of them.CONCLUSION: Using of sodium sulfonate was not effect on diameter and length of resin tags and thickness hybrid layer.